Identifikasi Karbon Monoksida Dalam Darah Pada Penjual Buah Di Jembatan Kembar Sungguminasa - Rustiah, Waode; Fatmawati, Andi; Ashrafiyah, Ashrafiyah (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Muhammadiyah Makassar, 2021)
The chemical compound of CO gas is a gas that has no color and contributes greatly to environmental pollution as a result of incomplete combustion of fuel produced from motor vehicles. Carbon monoxide is very dangerous (toxic, so it is often referred to as the